PERCEPTIONS OF VOCATIONAL SCHOOL STUDENTS ABOUT ONLINE LEARNING OF SYSTEMS AND REFRIGERATION INSTALLATIONS DURING THE COVID-19 - Putra, Halimar Wijaya (Universitas Pendidikan Indonesia, 2021)
The Covid-19 pandemic has forced the learning system in schools to change drastically from face-to-face meetings to online learners. The success rate of online learning in schools is only 25.3%. The purpose of this study was to find out how students' perceptions of online learning systems and refrigeration installations in the aspects of student infrastructure readiness in implementing online learning, the ability of educators and students, as well as their learning activities. This research uses descriptive quantitative method. The data collection technique used a closed questionnaire which was filled in by students of SMKN 1 Cimahi, the refrigeration and air conditioning engineering study program. The sample was the entire population of the study. The results of this study indicate that the student infrastructure readiness variable in implementing online learning is in the